Primary Education as an Input into Post-primary Education: A Neglected Benefit. - Appleton, S; Hoddinott, J; Knight, J (1996)
In some developing countries, private rates of return to primary education have fallen to low levels. An explanation is provided as to why this fall need not reduce the demand for primary education. Primary schooling is a necessary input into postprimary. In an educational system that is demand-constrained at the postprimary level, the 'prospect' of postprimary schooling raises the primary return above the rate as conventionally measured. An application of the model to two countries--Cote d'Ivoire and Uganda--doubles the primary rate of return in each case.